Culture, religion and humanism in T. S. Eliot’s thought - Zambrano Carballo, Pablo (Anales del Seminario de Historia de la Filosofía, 2011)
T. S. Eliot’s sociocultural thought has traditionally deserved less critical attention than his labour as a poet and literary critic. However, over the last decades, his role as one of Europe’s most respected and influential intellectuals has been widely attacked on ideological basis derived from his controversial ideas on social and cultural matters. This article aims at a reexamination of Eliot’s sociocultural proposals, focusing mainly on the links between culture, religion and humanism, in order to show that, although some of his polemical ideas may be well behind the times today, some others are still re-levant for the contemporary debate